Investigation of the effect of temperature on aging behavior of Fe-doped lead zirconate titanate - Promsawat, Napatporn; Promsawat, Methee; Janphuang, Pattanaphong; Marungsri, Boonruang; Luo, Zhenhua; Pojprapai, Soodkhet (World Scientific Publishing, 2017)
The aging degradation behavior of Fe-doped Lead zirconate titanate (PZT) subjected to different heat-treated temperatures was investigated over 1000 h. The aging degradation in the piezoelectric properties of PZT was indicated by the decrease in piezoelectric charge coefficient, electric field-induced strain and remanent polarization. It was found that the aging degradation became more pronounced at temperature above 50% of the PZT’s Curie temperature. A mathematical model based on the linear logarithmic stretched exponential function was applied to explain the aging behavior. A qualitative aging model based on polar macrodomain switchability was proposed.
Keywords: Aging; Temperature effect; piezoelectric; PZT